SYNTHESIS, IDENTIFICATION AND IN VITRO ANTITUMOUR PRESCREENING TEST OF TRIPHENYLTIN BENZOATE TOWARDS A HUMAN CERVICAL CARCINOMA CELL LINE, HeLa - Ida Bagus Putra Manuaba (Universitas Gadjah Mada, 2008)
In this study, triphenyltin benzoate was synthesized first, and followed by antitumor prescreening test of the compound towards a human cervical carcinoma cell line, HeLa. Three reaction steps were employed to obtain the compound needed, i.e. 1) synthesizing of tetraphenyltin compound via insitu phenilmagnesiumbromide Grignard reaction to tin(IV)chloride, 2) synthesizing triphenyltin chloride via redistribution reaction of tetraphenyltin to tin(IV) chloride without any solvent, the reaction completed depends on the temperature, in this case a good results was achieved at temperature 220 °C for 6 h, 3) finally, triphenyltin benzoate was produced through a methathetical reaction of triphenyltin chloride to an excess of sodium benzoate in ethanol. In vitro prescreening antitumour activity of the compound towards a human cervical tumour cell line, HeLa was carried out following an enzyme linked immunosorbent assays (ELISA). By this method, the test ended with good promising results. This indicates by the IC50 of 170 nM which is compared well to cisplatinum with IC50 950 nM.